Compliance with treatment: related-issues and insights for pharmacist intervention - Nilcéia Lopes da Silva; Eliane Ribeiro; João Luis Navarro; Antonio Carlos Zanini (Universidade de São Paulo, 2011)
Low patient compliance with pharmacotherapy remains one of the greatest challenges for success of treatments, especially in chronic diseases, since it can negatively influence treatment effectiveness and patient quality of life, increase health expenses and decrease productivity of the patient. Compliance is an important but complex issue in clinical practice. Its complexity begins with the difficulty in adopting terminology that can express its exact meaning. Moreover, many methods to evaluate compliance have been established but no consensus exists on which method should be considered the gold standard. Additionally, socioeconomic, disease and therapy-related factors, healthcare team and system related-factors and patient-related factors can simultaneously influence compliance levels. In this highly complex scenario, pharmacist interventions have been identified as an effective strategy to enhance patient compliance with treatment. The objectives of this paper were: (1) to provide useful information for pharmacists about issues related to compliance such as terminology and definitions; methods for measuring compliance and persistence; influencing factors and the impact of low compliance; and (2) to offer insight into how these healthcare professionals can effectively contribute toward improved compliance levels. A baixa adesão dos pacientes ao tratamento medicamentoso de doenças crônicas continua sendo um dos maiores desafios da medicina, por comprometer a efetividade do tratamento, repercutindo na qualidade de vida, aumentando os gastos com saúde e diminuindo a produtividade do indivíduo doente. O tema adesão é tão relevante para a prática clínica quanto complexo, a começar pelas tentativas de adoção de uma terminologia que expresse com exatidão o seu significado. Além disso, vários métodos para sua determinação foram estabelecidos sem, contudo, se chegar a um consenso sobre qual seria o "ótimo". Adicionalmente, as condições socioeconômicas, as características da doença, os tratamentos empregados, o sistema de saúde e seus profissionais ou o próprio paciente são alguns dos distintos fatores que influenciam, simultaneamente, o nível de adesão do paciente ao tratamento. Neste cenário de alta complexidade, intervenções realizadas pelo profissional farmacêutico têm sido apontadas como estratégias efetivas para o aumento dos níveis de adesão do paciente ao tratamento. Os objetivos deste artigo são: (1) fornecer aos farmacêuticos algumas informacões úteis relacionadas ao assunto adesão tais como: terminologia e definições, métodos para medir adesão e persistência, fatores influenciadores e impacto da baixa adesão; (2) fornecer algumas idéias a respeito de como estes profissionais de saúde podem efetivamente contribuir para a melhora dos níveis de adesão.